Reconciling Faith and Reason: Al-Bouti’s Defence of Roger Garaudy in the Context of Apostasy and Islamic Jurisprudence - Adam, Ibrahim Ilyasu (Journal of Quranic Sciences and Research, 2025)
This paper is, in a way, an assessment of an apologia of the offence of hadd written by Muhammad Said Ramadan al-Bouti (1929-2013) to defend Roger Garaudy (1913-2012) against the accusation of apostasy. It analyses the evidence presented by al-Bouti to support his arguments for exonerating Garaudy. Al-Bouti was a prominent Syrian scholar and one of the most influential Islamic jurists in the contemporary Arab world, and a Shafi’i jurist who believed in applying independent reasoning in his interpretation of rulings. In his efforts to preserve the Sufi concept of ‘interior form’ and ‘exterior behaviour’, al-Bouti combines the spirituality of Sufism with traditional legal rulings of fiqh to derive the power of a believer’s conformity with the Sharia. It was this hypothesis of reconciling Islamic mysticism with fiqh that helped his work to gain currency in the Islamic world. Roger Garaudy (1913-2012), on the other hand, was a French Marxist philosopher who converted to Islam in 1982/83, at the age of 70. His conversion to Islam was perceived in the West as indicating “the superiority of Islam over the West”. For this reason, the attack of Western scholars on him was interpreted as part of the West’s attack on Islam. However, Garaudy faced widespread criticism in the Muslim world after publishing his book Islam, to the extent that Muslim authors began to question the orthodoxy of his beliefs. The strongest assault came from the Saudi journal al-Mujallah in 1996, after Garaudy was interviewed by its correspondent in Paris. The article claims that Garaudy’s conversion to Islam was more or less superficial. This paper introduces brief details of al-Bouti’s life and his intellectual impact. Similarly, it highlights the Garaudy affair, his impact in the Muslim world, and the historical origin of the kufr accusation. Finally, it explores the main argument of al-Bouti in his defense case, making particular reference to the al-Mujallah article.